Hydrodynamics Alter the Tolerance of Autotrophic Biofilm Communities Toward Herbicides - Polst, Bastian H.; Anlanger, Christine; Risse-Buhl, Ute; Larras, Floriane; Hein, Thomas; Weitere, Markus; Schmitt-Jansen, Mechthild (Frontiers in Microbiology, 2018)
Multiple stressors pose potential risk to aquatic ecosystems and are the main reasons for failing ecological quality standards. However, mechanisms how multiple stressors act on aquatic communities and their functioning are poorly understood. This is especially true for two important stressors types, i.e. hydrodynamic alterations and toxicants. Here we perform mesocosm experiments in hydraulic flumes connected as a bypass to natural water bodies to test the interactive effects of both factors on natural (inoculated from streams water) biofilms. Biofilms, i.e. the community of autotrophic and heterotrophic microorganisms and their extracellular polymeric substances (EPS) in association with substratum, are a key player in streams. We hypothesized (i) that the tolerance of biofilms towards toxicants (the herbicide Prometryn) decreases with increasing hydraulic stress. As EPS is known as an absorber of chemicals, we hypothesize (ii) that the EPS to cell ratio correlates with both hydraulic stress and herbicide tolerance. Tolerance values were derived from concentration-response assays. Both, the herbicide tolerance and the biovolume of the EPS significantly correlated with the turbulent kinetic energy (TKE), while the diversity of diatoms (the dominant group within the stream biofilms) increased with flow velocity. This indicates that the positive effect of TKE on community tolerance was mediated by turbulence-induced changes in the EPS biovolume. This conclusion was supported by a second experiment, showing decreasing effects of the herbicide to a diatom biofilm (Nitzschia palea) with increasing content of artificial EPS. We conclude that increasing hydrodynamic forces in streams result in an increasing tolerance of microbial communities towards chemical pollution by changes in EPS-mediated bioavailability of toxicants.